AN ANALYSIS OF STUDENTS’ GRAMMATICAL ERRORS IN DESCRIPTIVE WRITING TEXT AT TENTH GRADE OF SMA DWIJENDRA DENPASAR IN THE ACADEMIC YEAR 2019/2020 - Yoktavianus Lerson; Gede Sutrisna (Widyasrama, 2020)
This research aimed at analysing the types of students’ grammatical errors in writing English descriptive text. The subjects of this study were 30 students of SMA Dwijendra kelas X IPS I. This research was descriptive qualitative. Writing test was used as the instrument to collect the data. Based on the result of data analysis which used the surface strategy taxonomy theory, it was found that there were 91 grammatical error consisting of 26 (28.57 %) Omission, 25 (27.47 %) Addition, 35 (38.46 %) Misformation, dan 5 (5.49 %) Misordering. Misformation was found to be the most dominant grammatical error which was apparently caused by intralingual factor.